Wastewater management alternatives in refugee camps - A. J. Cabrera Pacheco (Ingeniería, 2010)
According to the humanitarian response within a refugee camp situation, two phases occur most of the time, the emergency and a stabilization phase. The first one refers to relief operations when actions are taken in order to provide quick solutions to satisfy essential needs. The second one occurs once the situation is perceived as a non temporal camp; the quick solutions improvement and other needs are required and considered. Wastewater comes naturally along with the use of water in both stages of a refugee camp. It can be divided into three categories: domestic, human excreta and rainwater. There are multiple options for dealing with produced wastewater in a refugee camp considering that every option has to be analyzed by experts and consulted with refugee population since the solution should take into consideration not only costs and viability, but also cultural acceptance. When human excreta disposal and wastewater treatment solutions involve materials and experts; experts should train the population on how to manage and maintain the infrastructure before the humanitarian assistance leaves. Environmental sanitation is an important part within the refugee camp process in order to assure good health in the refugee population and to improve their life quality.